Retornados en Andalucía (España): una aproximación a los casos de Bélgica y la Argentina - Arjona Garrido, Ángeles; Checa Olmos, Juan Carlos (Pontificia Universidad Católica del Perú. Fondo Editorial, 2005)
Andalucía has been, traditionally, a starting point for emigration. Nowadays, the phenomenon has reversed and it receives populations from different parts of the world. To the foreign migrants we have to add the people who have returned to Andalucía. Here, we are going to study the return process from Belgium and Argentina. The results of the investigation show that the migrants who were in Belgium have experienced a circular migration with a clear intention of coming back, based, above all, on fulfillment or a failure to fulfill planned objectives. On the other hand, the case of the Latin American return is different. First of all, those who return are mostly the descendants of the emigrants. In second place, the initial migration has a definitive character; thus, there have been contextual factors—economic decline and lack of prospects—that have caused the return. In third place, the social networks have had a very minor role in the return to Andalucía.

Andalucía ha sido tradicionalmente una zona de expulsión de emigración. Actualmente el fenómeno se ha invertido y recibe población de multitud de latitudes diferentes. A los inmigrantes extranjeros hay que unir los retornados. Aquí vamos a estudiar los procesos de retorno desde la Argentina y Bélgica. Los resultados de la investigación muestran que los migrantes que estuvieron en Bélgica han experimentado una migración circular con una clara intención de retorno, basada, sobre todo, en la consecución de los objetivos previstos o el incumplimiento de estos. Por su lado, el caso del retorno latinoamericano es distinto. En primer lugar, retornan, sobre todo, los hijos de los emigrantes. En segundo lugar, la migración inicial tenía un carácter definitivo, por tanto, han sido los factores contextuales —declive económico y falta de expectativas— los que han provocado el retorno. En tercer lugar, las redes sociales han jugado un papel muy secundario en el regreso.
Returnees in Andalucía (Spain): an approach to the cases of Belgium and Argentina
Keywords: Migración; Migración internacional; Retorno; https://purl.org/pe-repo/ocde/ford#5.04.03